2021
DOI: 10.1021/acsomega.0c05699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perlite Particles on Barite Cement Properties

Abstract: Conventional heavy-weight oil and gas well cement systems formulated with barite exhibit high viscosities. Additionally, the heavy-weight powder tends to settle, causing density variation and disruption in the porosity of the hardened cement cores. Studies have shown that such problems can be mitigated by controlling the particle size distribution of the cement system. The main objective of this study is to evaluate the effect of perlite powder particles on the fluid and hardened properties of barite-based cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In the petroleum industry, some researchers evaluated perlite for potential usage in drilling fluids and oil well cement 22 25 . Adjei et al 23 investigated the impact of perlite powder on heavy-weight barite cement. It was observed that increasing the concentration of perlite powder led to a decrease in plastic viscosity and an increase in yield point and gel strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the petroleum industry, some researchers evaluated perlite for potential usage in drilling fluids and oil well cement 22 25 . Adjei et al 23 investigated the impact of perlite powder on heavy-weight barite cement. It was observed that increasing the concentration of perlite powder led to a decrease in plastic viscosity and an increase in yield point and gel strength.…”
Section: Introductionmentioning
confidence: 99%